Răspuns :
[tex] \frac{x}{3} [/tex] = [tex] \frac{y}{4} [/tex]
y= 14+x
acum inlocuiesti
[tex] \frac{x}{3} [/tex] = [tex] \frac{14+x}{4} [/tex]
faci produsul mezilor egal cu produsul extremilor si o sa ai
4x= 3(14+x)
4x= 42+ 3x
4x-3x=42
x=42
si y = 42+14= 56 ( pentru ca zice ca e de 14 ori mai mare)
Deci
x=42
y=56
y= 14+x
acum inlocuiesti
[tex] \frac{x}{3} [/tex] = [tex] \frac{14+x}{4} [/tex]
faci produsul mezilor egal cu produsul extremilor si o sa ai
4x= 3(14+x)
4x= 42+ 3x
4x-3x=42
x=42
si y = 42+14= 56 ( pentru ca zice ca e de 14 ori mai mare)
Deci
x=42
y=56